A trajetória da educação matemática brasileira: um olhar por meio dos livros didáticos Matemática (1982) e Matemática e realidade (2005) - Santos, Ângela Cristina dos (2008)
This survey aims to show the process of disciplinarization of Mathematics in Brazil, through the perceived changes and stays in the manual teaching. The investigation comes within the field of history of Disciplines School, in particular, Mathematics Education. The textbook of Mathematics was part of the historic changes which passed by the Brazil and certifies these changes in teaching. The research was divided into two parts, namely: the historical research and comparative research. This last was held in two collections of textbooks, Gelson Iezzi, Osvaldo Dolce and Antonio Machado, published at different times: Mathematics" (1982) and Mathematics and Reality" (2005),. The historical research shows that the development of Mathematics School also did not occur in a linear form, its consolidation as a discipline was the result of tensions, interests and demands of a particular historical time and in the aspect of social, cultural, religious, political and/or teaching. The Mathematics Education in Brazil had its origin in military school and went through several phases initially characterized by uncritical emphasis on training and practice, then as an instrument of social distinction, rationalization and, currently, training citizen. Independently, the changes for which the teaching of Mathematics became, depended almost exclusively of historical time, which defined its purpose. "Mathematics" was published at a time of political transition from dictatorship to the beginning of a democratic politics. Already "Mathematics and Reality" was published in a moment of democratic consolidation. The comparative analysis showed that there were significant changes in the teaching of mathematics in the period from 1982 to 2005, mainly in relation to the resolution of problems. These changes were mainly influenced by the curriculum built from the existing laws of the time, and in the collection of 2005, the proposed curriculum and methodological parameters of the National Curriculum. It was possible to identify issues involving the methods, realizing the importance of distinguishing the content and goals of discipline in different moments of Brazilian education, which allowed inferred on the methodological attitude of teachers using the books in time. It is expected that the results presented are important for historical research of disciplines and enabling the understanding of the purposes of teaching of mathematics to the present and also the origin and the "why" of the practices now available and used in the classroom, opening thus a range of possibilities for change.